Air Contamination and Ecological Information Disclosure From South Africa’s High Energy Consumption Industries - Thomas NYAHUNA; Mishelle DOORASAMY (International Journal of Environmental, Sustainability, and Social Science, 2022)
Globally, South Africa is currently amongst the countries with the poorest air pollution. Recently, organization ecological information disclosure has turned out to be a progressively more prevalent method for ecological by-laws. However, at the moment, there is an absence of empirical confirmation on the organization ecological information disclosure effects of air contamination. This research investigates the relationship between air contamination and organization ecological information disclosure applying cross sectional data gathered from listed South African companies in high energy consumption sectors from 2015 to 2021. The findings disclose that the link between air contamination and organization ecological information disclosure is substantially adverse. The Northern province has huge effects on organization ecological information disclosure in comparison with the Eastern province. Furthermore, effect air contamination has on organization ecological information disclosure also varies in companies situated in province with various corporate ecological information disclosure transparency. This study makes available a portrait of the interaction between air contamination and ecological information disclosure expansion in emerging economies such as South Africa.